Portfolio Review of World Bank Lending for Communicable Disease Control - Martin, Gayle H. (Washington, DC: World Bank, 2017)
Communicable diseases are a major burden of disease among the poor, and communicable disease control is central to achieving the Millennium Development Goals (MDG) adopted at the Millennium Summit in 2000. Over the years communicable disease control has featured prominently in several strategic Bank documents. In the 1997 Health, Nutrition, and Population (HNP) Sector Strategy communicable disease control was one of the essential HNP priorities. The 2007 HNP sector strategy made extensive reference to the need for synergy between communicable disease control (especially disease-specific projects) and health system strengthening. Communicable diseases also feature as one of four priority areas in the global public good strategic theme in the Bank's six strategic themes identified in 2007. This paper is organized into five chapters. The following chapter describes the sample of projects covered in this review and the methodology. The results of the review of approved and closed projects follow in the third and forth chapters, respectively, and the last chapter summarizes the conclusions.